The Genesis of a Policy Defining and Defending Australia's National Interest in the Asia-Pacific, 1921-57 - Cuffe, Honae (ANU Press, 2021)
The years 1921-57 marked a period of immense upheaval for Australia as the nation navigated economic crises, the threat of aggressive Japanese expansion and shifting power distributions with the world transitioning from British leadership to that of the US. This book offers a reassessment of Australia's foreign policy origins and maturation during these tumultuous years. Successive Australian governments carefully observed these global and regional forces. The policy that developed in response was an integrated one-that is, one that sought to balance Australia's particular geopolitical circumstances with great power relationships and, in assessing the value of these relationships, ensure that the nation's trade, security and diplomatic interests were served. Amid the economic and strategic uncertainty of the interwar years, the Australian government acknowledged the shifting power distributions in the global and Asia-Pacific orders and that neither the policies of Britain nor the US completely served the national interest. The nation, accordingly, sought to intervene within the policies of the great powers to ensure its particular interests were secured. This geopolitically informed, interventionist approach, which had its genesis in the 1930s, is traced throughout the 1940s and 1950s, highlighting Australia's gradual and uneven transition from the British world order to that of the US and the frank assessments made about which relationship best served Australia's interests. The Genesis of a Policy identifies a comprehensive and pragmatic approach-albeit not always effectively executed-in Australian foreign policy tradition that has not been previously examined.